Passing the Crossroad: An Overview on Issues and Challenges of the University Education in Sri Lanka (Global Journal of Human-Social Science, 2018)
In spite of recent developments in the higher education in Sri Lanka it has undergone a tremendous transition that somehow resulted in a crisis The review of this issue through a critical narrative analysis shows that some of the issues hidden behind more conspicuous ones like increasing gender-based violence and ragging are more detrimental The hardening challenge is that many students in public-funded universities have lost enthusiasm to learn as there is no conducive environment and further this is crystallized due to lack of quality in pedagogy narrow and shortsighted perspectives of the contribution of universities to the contemporary world These issues would challenge the existing higher education process in Sri Lanka which in turn signals the policymakers including academics to work fast with care and to search for innovative strategies to tackle with them while minimizing the severe impact of existing issues on higher education
Keywords: emancipatory education; globalization; higher education; issues and crises; quality of pedagogy